Performance analysis and design of bolted connections in modularized prefabricated steel structures. (June 2017) - Liu, X.C.; Pu, S.H.; Zhang, A.L.; Zhan, X.X.
Abstract: The present study proposes a new-type all-bolted connection that can be used to connect trusses to columns and columns to columns on site in modularized prefabricated multi-rise and high-rise steel structures. The proposed connection connects columns through flanges, connects trusses to columns through cover plates that extend from the flanges and through vertical connecting plates and joint flitches. The stiffness of the connection can be controlled by adjusting the number or size of the bolts and undergoes step-like change as the load changes. Therefore, the connection can be rigid during weak earthquake, while the cover plates can slip relative to the chord members during strong earthquake, thereby dissipating energy. The FEA results was compared with experimental results and showed good agreement at all stages of loading, then the static performance of six connections with different friction coefficient or size of components were studied by FEA. The FEA results were used to determine mechanical properties of the connections that were difficult to obtain from the tests, such as the changing rule of the bolt tension, the stress distribution of bolt, the contact force on various contact surface, and the pressure on the wall of bolt hole, as well as the effects of friction coefficient on the performance of the connections. The mechanical model of the connection was established and the mechanical mechanism of the connection was got. Furthermore, simplified calculating formulas for the connection under slip state, yield state and ultimate state were proposed respectively. Graphical abstract: Highlights: Stiffness of connection can be controlled by adjusting the number or size of bolts. Failure mode and hysteretic loop of connection got by FEA were compared with test. Mechanical properties that were difficult to obtain from tests were got by FEA. Contact force and slip rule was obtained and mechanical model was established by FEA. Simplified calculating formulas for connection under various states were proposed.